The radiation of macaques out of Africa: Evidence from mitogenome divergence times and the fossil record. Issue 133 (August 2019) - Roos, Christian; Kothe, Maximilian; Alba, David M.; Delson, Eric; Zinner, Dietmar
Abstract: Fossil evidence indicates that numerous catarrhine clades of African origin expanded or shifted their ranges into Eurasia, among them macaques Macaca Lacépède, 1799. Macaques represent the sister taxon of African papionins and can thus be used as a model comparing an 'out-of-Africa' with an intra-African, e.g., baboons— Papio Erxleben, 1777 evolutionary history. The first step for such a comparison is to establish a well-resolved phylogeny of macaques with reliably estimated divergence times and to compare it with that of baboons and the fossil record. Therefore, we used mitochondrial (mtDNA) genome data deposited in GenBank of 16 out of 23 extant macaque species and of all six baboon taxa. We reconstructed phylogenetic trees using maximum-likelihood and Bayesian inferences and dated differentiation events using three fossil-based calibration sets. The obtained tree topology is in agreement with findings from earlier mtDNA studies, but yielded stronger nodal supports. We observed some para- and polyphylies in macaques and baboons, suggesting that ancient gene flow among divergent lineages has been common in both genera. Our divergence time estimates are in broad agreement with earlier findings and with the fossil record. Macaques started to diversify 7.0–6.7 Ma, followed by a stepwise radiation into several species groups in Asia, whereas baboons commenced diversification around 2.2 Ma. Accordingly, divergence of species groups and species in macaques clearly predates divergences in baboons. Based on our phylogenetic results with estimated divergence times and the recorded chronostratigraphic ranges of extinct macaque and baboon taxa, we compare the evolutionary radiations of both genera from paleobiogeographic and adaptive viewpoints.